Informal Employment Impact on Social and Economic Development of Russian Federation Entities - E. I. Dubravskaya (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
To make managerial decisions on labour market regulation on the regional level it is necessary to have an objective statistic estimation of interconnection between informal employment and indicators of social and economic development. The article describes preconditions of forming a complex system of indicators on the basis of documents of strategic planning and analysis of works by Russian and overseas researchers dealing with issues of informal employment. Informal employment is an independent field of research that attracts scientists from different spheres and disciplines: from economics and anthropology to gender research, politology, sociology and city planning. Due to the fact that sizes and composition of informal employment, causes of its arising and consequences, lines of impact and interconnection with other figures are different, the author took analysis of documents of strategic planning and goals of national development of the Russian Federation up to 2024 as a starting point for shaping the structure of the system of indicators. In the research indicators of social and economic development were grouped by blocks corresponding to lines in national projects and supplemented by the block of indicators characterizing the macro-economic situation. This categorization based on priorities of national development fosters conclusion drawing with due regard to human capital, comfortable environment for life and economic growth.